WAYS OF COMPILING LEVEL OBJECTIVES ON IRRATIONAL EQUATIONS AND INEQUALITIES - Kaldan С.; Kasenov С.Е.; Sh.T. Rakhmet Ш.Т.; Sarsenbayevа А.Н.; Imanbaev Б.М. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
This article focuses on the use of the level-differentiated teaching methodology in solving irrational equations and inequalities in the school course. In the general classroom, there are students of different development and preparation level, progress and learning attitude, interest and perception. The teacher faces various difficulties when organizing traditional teaching. Therefore, it is necessary to use level differentiation so that the students do not stay at the same level, but on the contrary, the level of the student rises and his interest in the subject increases. Solving irrational equations and inequalities is one of the difficult topics in the school mathematics course. In the introduction of the article, we talk about the definition of differentiated education and the three divided levels. Further, focusing on the way of generalization of problems for irrational equations and inequalities, problems were divided according to the method, and their solutions were analyzed and written.